Desenvolvimento de um Modelo de Negócio para uma Plataforma Colaborativa de Conteúdos Audiovisuais de Cariz Científico - Ana Francisca de Nóbrega Malça Gonçalves Tété (2019)
This dissertation falls within the scope of the Project CHIC- Cooperative Holistic View on Internet and Content, where INESC TEC and FEUP are partners. The purpose of this dissertation was to develop a business model for the CHIC Science Platform, which is a collaborative platform of scientific audiovisual content, ally to a dynamic strategy between crucial stakeholders of the business, namely the ones involved in production, creation and consumption of these contents. This business model will help the CHIC Science Platform structure the business more easily in order to achieve its goal, which is sustainability. Besides, it will make the platform reflect about its business plans as well as its partners, clients and market. Initially, a theoretical study was carried out on the relevant concepts that would support the development of this work. It was begun with the concept of business models on digital platforms, focusing on the general concept of "business model" and "business models on digital platforms", and it was ended with the concept of "community dynamics". Furthermore, it was studied the structure of the business model to understand which one could possibly be adapted to the CHIC Scientific Platform. Then, it was analyzed crucial information for the development of the business model, namely stakeholders, national and international market and sustainability. Based on this analysis, a dynamic strategy, a sustainability plan and a business model were developed.